Affective evaluation of consciously perceived emotional faces reveals a “correct attribution effect” - Brunet, Nicolas M. (Frontiers in Psychology, 2023)
The strength of the affective priming effect is influenced by various factors, including the duration of the prime. Surprisingly, short-duration primes that are around the threshold for conscious awareness typically result in stronger effects compared to long-duration primes. The misattribution effect theory suggest that subliminal primes do not provide sufficient cognitive processing time for the affective feeling to be attributed to the prime. Instead, the neutral target being evaluated is credited for the affective experience. In everyday social interactions, we shift our gaze from one face to another, typically contemplating each face for only a few seconds. It is reasonable to assume that no affective priming takes place during such interactions. To investigate whether this is indeed the case, participants were asked to rate the valence of faces displayed one by one. Each face image simultaneously served as both a target (primed by the previous trial) and a prime (for the next trial). Depending on the participant’s response time, images were typically displayed for about 1–2 s. As predicted by the misattribution effect theory, neutral targets were not affected by positive affective priming. However, non-neutral targets showed a robust priming effect, with emotional faces being perceived as even more negative or positive when the previously seen face was emotionally congruent. These results suggest that a “correct attribution effect” modulates how we perceive faces, continuously impacting our social interactions. Given the importance of faces in social communication, these findings have wide-ranging implications.